A "Labyrinth of Linkages" in Tolstoy's "Anna Karenina" - Browning, Gary L. (Studies in Russian and Slavic Literatures, Cultures, and History, 2010)
The renowned Russian writer Leo Tolstoy created a realistic masterpiece in Anna Karenina (1878). In the same work, moreover, he utilized allegory and symbol to an extent and at a level of sophistication unknown in his other works. In Browning's study, the author identifies and analyzes previously unnoticed or only briefly mentioned "linkages and keystones" found in two highly developed clusters of symbols, arising from Anna's momentous train ride and peasant nightmares, and of allegories, rooted in Vronsky's disastrous steeplechase. Within this labyrinth of symbol and allegory lies embedded much of the novel's most significant meaning. This study will be of particular interest to students and scholars of Russian literature, Tolstoy, symbol, allegory, structuralism, and moral criticism.